EKSPRESI PENOLAKAN PRAGMATIK ANAK USIA 2—3 TAHUN - Farida Yufarlina Rosita; Dwi Kuniasih (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2018)
This study aims to explore the forms of expression of pragmataik rejection in children aged 2—3 years. In addition, this study also aims to explain the factors that influence the acquisition of the language of the child so as to act pragmatic speech. The method used in this research is qualitative descriptive. Qualitative descriptive method is a method that attempts to describe and interpret objects as they are. Data collection methods are carried out with several techniques, namely, see, record, and note. The results of this study indicate the existence of two forms of expression of rejection that is explicit and implicit. The form of exclusion is classified into nonverbal and declarative rejection. There are several forms of implicit refusal: implicit refusal by reason of, interrogative implicit refusal, alternative implicit rejection, implicit declarative rejection, implicit rejection with demand. In addition, the results of this study indicate a factor that affects the pragmatic ability of children 2—3 years, namely natural factors, cognitive development, socioeconomic, and family.